Effect of Chloride Salinity and Boron on Germination, Growth and Mineral Composition of Chickpea (Cicer Arietinuml.) - Yadav, H D; Yadav, O P; Dhankar, O P; Oswal, M C (Annals of Arid Zone, 2016)
In a pot culture experiment on a loamy sand, chickpea germination, dry matter yield and mineral composition at six weeks were observed as a function of increasing soil boron (0.6, 2.3,4.3,6.2 and 8.1 ppm) at five salinity levels ( .4, 1.5,4.3, 6.2 and 8.5 dSm-1 the dry matter yield decreased from 5.12 to 1.55 gpot. Concentration of Ca. Mg and Na in tissues increased and that of K and B decreased with increased soil salinity. Application of boron also inhibited germination and decreased dry matter yield. At 0.6 and 8.1 ppm soil boron, the per cent germination and dry matter yield were 78 and 61%; 4.91 and 1.78 g/pot, respectively. Soil boron resulted in luxury consumption of Na and thereby reduced K uptake. The saline soils with higher amounts of boron were found more harmful to germination and growth of chickpea than saline soils with lower amounts of boron.